En sykepleiers erfaringer i møte med pårørende - og seg selv - Betty-Ann Solvoll; Gøril Ursin; Berit Støre Brinchmann; Anders Lindseth (Septentrio Academic Publishing, 2013)
Abstract A nurse's experience of encountering the next of kin - and herself. The purpose of this scientific essay is to show how emotions embedded in events and experiences may be significant to nursing practice. Through dialogs and reflections it is possible to relate actively to our own emotions and thus reveal important knowledge about oneself and others. The story in this essay is told by the nursing staff in a reflection group from a rehabilitation department. The reflections were on the staff's experiences of ethical challenges in their everyday practice. Based on the conversation, we have written a story. The story is examined through a critical investigating method, using a dialogical and hermeneutical method. The analysis in this essay shows how challenging events may give a greater understanding of the persons acting in practice by systematically reflect on experiences. The essay further demonstrates how systematic investigation on narratives contributes significantly to practical knowledge. Personal experiences may be transformed into public knowledge.